Akad dalam Filsafat Ekonomi Islam - Mohammad Syarifuddin Amarullah; A. Hasan Ridwan; A. Yunus Rusyana (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2025)
The concept of 'aqd (contract) has a central position in the building of al-fikr al-iqtiṣādī al-islāmī (Islamic economic philosophy), because it is the basis for legitimacy in economic interactions built on the principles of justice (al-'adālah) and willingness (al-tarāḍī). This research aims to examine the concept of contracts from the perspective of Islamic economic philosophy through a normative juridical approach with a literature study method. The results of the study show that contracts in Islam are not merely formal legal agreements, but are moral ties that reflect transcendental responsibility to God (ta'abbud). The contract becomes a manifestation of al-amānah, al-'adl, and al-maslahah values in Islamic economic practices. These findings reinforce the importance of revitalizing the concept of akad in designing an ethical and equitable Islamic economic system.